Taxonomic study of Ruprechtia C.A. Mey. (Polygonaceae) in Brazil - de Melo, Efigênia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
Taxonomic study of the genus Ruprechtia C.A. Mey. (Polygonaceae) in Brazil was done. The genre is american and has 37 species distributed from southern Mexico to Argentina and Uruguay. The species are trees, shrubs, lianas or scandent, with alternate leaves and ocreas at the base of the petiole. The results presented were based on morphological characters, based on the analysis of collections of national and foreign herbaria, and field work to observe the populations in their natural environment. The taxonomic treatment includes nomenclatural update, synonymizations, morphological descriptions, comments on the geographical distribution and illustrations for most species. Fifteen species are recognized and two new synonyms are proposed in addition to expanding the distribution area for four species.